IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SD TAMANSISWA MEDAN - Azzahra, Chanisah; Siregar, Afrida Damai Yanti; Siregar, Fitri Handayani; Siregar, Rizka Fadhila; Siregar, Waliyul Maulana (Universitas Negeri Medan, 2024)
Pancasila functions as the foundation of Indonesia's national values, which drive societal and governmental functions in all domains. This research aims to assess the extent to which Pancasila values are implemented and the role of teachers and schools in supporting the integration of these values, especially in the context of classroom learning. Using quantitative methods with a descriptive approach, this research seeks to describe and analyze data regarding the implementation of Pancasila values in elementary schools (SD). This research involved 20 fifth grade students at Tamansiswa Elementary School in Medan as research subjects. The instruments used in this research were observation and interviews. Observation results show that the application of Pancasila values to students at the elementary school level is very important, considering that it is at this stage that students receive the basics of education from teachers, including basic skills such as correct reading and writing, as well as an understanding of Pancasila values.